Induction of larval settlement and metamorphosis of Mercenaria mercenaria using excess Ca2＋and Mg2+alone or in combination - Jian Liang; Bajun Shi; Yongren Li; Shuang Liang; Huiru Liu; Wei Dai; Yongjun Guo (Aquaculture Reports)
The induction effect of excess Ca2+ and Mg2+ alone or in combination on settlement and metamorphosis of Mercenaria mercenaria larvae were studied by initiating ion supplementation at two different developmental stages. Pediveligers were supplemented with a range of excess Ca2+ (0–18 mM), Mg2+ (0–40 mM) and Ca2＋/ Mg2+ (0–7.5/0–37.5 mM), respectively. Results showed excess Ca2+ and Mg2+ alone or in combination could induce settlement and metamorphosis of M. mercenaria. The optimal concentrations of Ca2+, Mg2+, and Ca2+/Mg2+ were 10 mM, 20 mM and 3.125/15.625 mM, respectively. The supplementation of the above optimal concentration of ions from D-shaped larvae stage also significantly induced larval metamorphosis (P < 0.05), and at the same concentration, the induction effect was better than that initiating from pediveliger stage. In addition, compared with the control group, ion supplementation from D-shaped larvae stage significantly increased the survival rate of pediveligers (P < 0.05) and prolonged the planktonic duration. The longer the planktonic duration, the larger the larval size at the end of the planktonic stage and the higher metamorphosis rate of larvae. In the hatchery seed production of M. mercenaria, it is recommended to supplement 3.125/15.625 mM Ca2＋/ Mg2+ from the D-shaped larvae stage to induce the settlement and metamorphosis.